Modeling the signaling value of the GED with an application to an exogenous passing standard increase in Texas - Magnus Lofstrom; John Tyler (Institute for the Study of Labor (IZA), 2007)
In this paper we develop a simple model of the signaling value of the GED credential. The model illustrates necessary assumptions for a difference-in-difference estimator, which uses a change in the GED passing standard, to yield unbiased estimates of the signaling value of the GED for marginal passers. We apply the model to the national 1997 passing standard increase which affected GED test takers in Texas. We utilize unique data from the Texas Schools Micro Data Panel (TSMP) which contain demographic and GED test score information from the Texas Education Agency linked to pre- and post-test taking Unemployment Insurance quarterly wage records from the Texas Workforce Commission. Comparing Texas dropouts who acquired a GED before the passing standard was raised in 1997 to dropouts with the same test scores who failed the GED exams after the passing standard hike, we find no evidence of a positive GED signaling effect on earnings. However, we find some evidence which suggest that our finding may be due to the low GED passing threshold that existed in Texas for an extended period.
Keywords: 330; Absolventen; Bildungsniveau; Signalling; Bildungsertrag; Texas; USA